Trends in river herring environmental DNA in two North Carolina river systems - Seth M. Gibbons; Chase G. Spicer; Sara Roozbehi; Chequita N. Brooks; Cory S. Joyner; Michael S. Brewer; Roger A. Rulifson; Erin K. Field (PLoS ONE, 2026)
River herring (Blueback Herring [ Alosa aestivalis ] and Alewife [ A. pseudoharengus ]), were once abundant in North Carolina waters and were an economically important commercial fishery. Both populations have declined in recent history due to habitat loss, overfishing, and river alterations. Eastern North Carolina’s turbid and large river systems make traditional sampling difficult; thus, a rapid and accurate method for quantifying spawning populations is needed. The use of environmental DNA (eDNA) to detect river herring has been successfully applied to other watersheds across the Atlantic Coast. To determine if eDNA techniques could be applied to turbid watersheds to monitor river herring movement during the spawning season, weekly water sampling was performed at eight sites along the Neuse and Tar-Pamlico Rivers in North Carolina. Sampling for eDNA at two locations along the Neuse River were conducted in tandem with traditional electrofishing surveys to compare trends in river herring abundance between methods. The results indicate that both river herring eDNA concentrations and fish counts using electrofishing increased in the first three weeks of the spawning season. During the second half of the spawning season, eDNA concentrations remained high while fish abundances decreased. These results suggest that eDNA may be more consistent with electrofishing early in the spawning season while it may detect eDNA from juveniles, larvae, and persistent ambient eDNA later in the spawning season after adults have left the system. Sampling multiple locations along the rivers also indicated that the eDNA trends were consistent between different river systems. Sampling location where eDNA was collected mattered, as sites further upriver were more consistent in eDNA trends between river systems, and are likely better for long-term monitoring, compared to downstream locations. The results of this work help lay the foundation for the application of eDNA for future monitoring efforts in turbid waters, including North Carolina watersheds.